Peran Customer Mindfulness dan Perceived Service Quality Terhadap Customer Purchase Intention - Laurencia, Steffy; Abdurrahman, Abdurrahman (Ikatan Da'i Indonesia, 2025)
In the current digital era, the younger generation increasingly relies on digital services in meeting their daily transporation needs, one of which through online vechicle booking applications such as Grab. This study aims to analyze the effect of mindfulness and perceived service quality on customer’s purchase intention, by considering the mediating role of perceived usefulness and perceived ease of use. This study used purposive sampling method by involving 150 respondents who live in Jakarta and are active users of Grab application Data was collected through an online survey and analyzed using PLS-SEM software assistance. The results showed that mindfulness has a positive effect on perceived usefulness and perceived ease of use. Furthermore, perceived usefulness and perceived ease of use are also proven to have a possitive effect on customer’s purchase intention. Meanwhile, perceived service quality does not have a significant effect on perceived usefulness and customer’s purchase intention. In addition, mindfulness also indirectly affects customer’s purchase intention through perceived usefulness and perceived ease of use as a mediating variables. These findings emphasize that customer mindfulness of a digital service features and benefits plays a key role in improving customer’s purchase intention. Practically, ride-hailing companies are advised to simplify application features and educate users to be more aware of service benefits, in order to strengthen consumer engagement and loyalty.